Patai's Chemistry of Functional Groups 2010
DOI: 10.1002/9780470682531.pat0516
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrogen: A Study of Nitrogen/Oxygen Heterocycles with NO and OO or NOO Bonding

Abstract: Hydroxylamines, oximes and hydroxamic acids that are also associated with a peroxy group are considered. To be both brief and selective, only those species that are heterocycles with NO and OO or NOO bonding are included. Plausible, but inadequately characterized, classes of compounds are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 128 publications
1
6
0
Order By: Relevance
“…CHCl 3 contains trace ethanol as a stabilizer, which was not removed. The results were reproducible and nearly identical in either CHCl 3 or CH 3 ] that was synthesized as described previously. 7 Computational Methods.…”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…CHCl 3 contains trace ethanol as a stabilizer, which was not removed. The results were reproducible and nearly identical in either CHCl 3 or CH 3 ] that was synthesized as described previously. 7 Computational Methods.…”
Section: Methodssupporting
confidence: 52%
“…Despite the decades-long interest in N-nitrosamine organic chemistry and toxicity, 1,2 no photochemical O-atom exchange process with molecular oxygen has been reported. One paper 3 speculated that an O-atom exchange between singlet oxygen ( 1 O 2 ) and N-nitrosamine would proceed by a 1,2,3,4trioxazetidine intermediate (cycloNO 3 species) (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“… and so must be “approximated.” There are no species at all with measured enthalpies of formation with either –O–O–N– or –O–N–N– functionalities should we sensibly ignore multiply bonded species such as peroxynitrites and azoxy compounds (for a review of the thermochemistry of hydroxylamine derivatives and a survey of cyclic species with the –O–O–N– functionality see Refs. and respectively). Said differently, while ∆ f H 0 ( 4 ) = C–(N)(O)(H) 2 + N–(N)(O)(C) + O–(O)(N) + O–(O)(C) + N–(N)(H) 2 + ring correction, but the group increments C–(N)(O)(H) 2 , O–(O)(N) and N–(N)(O)(C) and the ring correction must be derived de novo for the current study.…”
Section: Resultsmentioning
confidence: 88%
“…It is suggested that this thermal reaction might proceed via corresponding nitroso oxide or directly 100,101 . (5) Inui and colleagues attempted to detect dioxaziridine by IR spectroscopy upon photolysis of 4-nitrophenyl azide in a xenon matrix doped with oxygen at 50 K 94 . The formation of cis-and trans-isomers of the corresponding nitroso oxide was registered.…”
Section: Study Of Mechanism Of Transformations Of Nitroso Oxides In Lmentioning
confidence: 99%
“…At the present time, there are several reviews devoted to organic azides 1, 2 , dioxygen species XO 2 3, 4 , and nitrogen-oxygen heterocyclic compounds 5 , in which some attention was paid to nitroso oxides. They possess very interesting properties, significant progress in the study of which was achieved in recent years.…”
Section: Introductionmentioning
confidence: 99%